Limited Efficacy of Salvage R-ICE Therapy in Relapsed Diffuse Large B-Cell Lymphoma: A Real-World Study from Iraq - Mohamed, Aamer Shareef (Asian Pacific Journal of Cancer Biology, 2026)
Background: Relapsed or refractory diffuse large B-cell lymphoma (DLBCL) remains challenging to treat. Despite widespread use of salvage R-ICE, real-world data on outcomes and response predictors are limited, with a notable scarcity of regional data from low-resource settings. Objectives: This study aimed to characterize the profile and outcomes of relapsed DLBCL patients, evaluate the efficacy of salvage R-ICE therapy, and identify factors associated with treatment response and overall survival. Methods and Materials: Data from 59 consecutive adult patients with recurrent DLBCL at a tertiary center in Iraq (2017–2022) were analyzed in this retrospective cohort research. Of these, 49 were treated with salvage R-ICE. Data on survival, treatment response, laboratory, and clinical parameters were extracted. Logistic regression, log-rank tests, and Kaplan-Meier survival curves were among the statistical analyses used. Results: The cohort had a median age of 54 years, with 52.5% presenting with stage IV disease. Most patients were poor responders to first-line R-CHOP (interim: 71.2%; end-of-therapy: 79.7%). The response rate to R-ICE after 2 cycles was low (10.2%). Receiving R-ICE did not confer a survival benefit compared to no R-ICE (mean survival 15.82 vs. 14.5 months, p=0.877). However, patients who responded to R-ICE had significantly longer survival than non-responders (34.4 vs. 13.7 months, p=0.002). Response to first-line R-CHOP was a powerful prognostic factor for overall survival after relapse (p<0.001). No baseline clinical or laboratory factor significantly predicted R-ICE response, though a non-significant trend suggested prior chemosensitivity may be associated. Conclusion: Salvage R-ICE showed limited efficacy in this real-world cohort. Response to R-ICE, though uncommon (10.2%), was associated with marked survival advantage. Initial chemosensitivity to R-CHOP remained a key prognostic factor. However, the small number of responders limited statistical power and precludes definitive conclusions. These findings underscore the urgent need for improved patient selection strategies and the integration of novel therapies, such as CAR-T cells and bispecific antibodies, for patients unlikely to benefit from conventional salvage chemotherapy. These results emphasize the limited effectiveness of traditional salvage chemotherapy in unselected populations and highlight the necessity of predictive biomarkers to inform more individualized treatment selection.